The role of faculty in reducing academic dishonesty among engineering students. Issue 12 (1st December 2020) - Chirikov, Igor; Shmeleva, Evgeniia; Loyalka, Prashant
ABSTRACT: University faculty are frequently tasked with promoting academic honesty among students. However, there is little reliable evidence about whether faculty actions can prevent academic dishonesty. The purpose of this study is to examine whether more severe punishments from faculty can reduce academic dishonesty among students. We analyze nationally representative, longitudinal and matched data on engineering undergraduates and faculty from 33 universities in Russia, and document extremely high and increasing rates of dishonest academic attitudes among students, especially among the higher achieving students. In the first two years of study the proportion of students tolerant to academic dishonesty increases by 5 percentage points. We then show that despite the tide of increasing academic dishonesty among students, more severe punishments from faculty significantly and substantially improve student attitudes towards academic dishonesty. Taken together, the findings emphasize the importance of strengthening the role of faculty in promoting academic honesty among students.